Predisposing factors and predictors of IgG and IgM antibody seroprevalence against Toxoplasma gondii in medical students from a coastal university in Ecuador - Garcet, Yoiler Batista; William, Luciano Salazar, César; Mendoza, Lauricia Jacqueline Macías; Menendez, Marieta del Jesús Azua; Santana, Caleb Isaac Chilán (Journal of Posthumanism, 2025)
Background: Toxoplasmosis, caused by Toxoplasma gondii, poses substantial risk in pregnancy and immunocompromise. Medical students face combined environmental exposure, variable hygiene, and academic practices. Objective: To examine predisposing factors associated with IgG/IgM seroprevalence in students from a coastal Ecuadorian university and identify independent predictors. Methods: Cross-sectional study of 640 randomly selected students; validated questionnaire (α=0.927) and ELISA for IgG/IgM. Descriptive statistics, chi-square/Fisher, Mann-Whitney U, and logistic regression were applied. Results: Seroprevalence 58.3% (IgM 39.7%; IgG 27.5%). Associations: rural residence, cat contact, undercooked meat, untreated water, and poor food hygiene. Predictors: untreated water (OR=21.9; 95%CI 13.9–34.6), cat contact (OR=3.2; 2.0–5.0), and undercooked meat (OR=2.18; 1.39–3.41). Conclusions: Findings indicate ongoing transmission in university settings. Priorities include ensuring safe water, strengthening food hygiene, and biosafety training. The predictive model supports targeted prevention and surveillance strategies.